Yttria-Doped Zirconia-Hydroxyapatite Composite Coating on Cp-Ti Implants by Biomimetic Method - Karakas, Aysu; Yoruc, A. Binnaz Hazer; Erdogan, Duygu Ceylan; Elkoca, Oktay (TRANS TECH PUBLICATIONS LTD, 2012)
Titanium (Ti) and Ti-alloys are often used in dental and orthopedic applications because of their good mechanical properties and biocompatibility. The advantages of Ti and Ti-alloys are its superior corrosion resistance, high fatigue strength and low elastic modulus which reduce stress shielding. Morover biocompatibility of them can be improved coating with bioceramics such as hydroxyapatite (HA) or other ceramic composites. The hydroxyapatite [Ca-10(PO4)(6)(OH)(2), HA] is frequently used as a coating material on the surfaces of Ti-based medical implants to improve the bone fixation and thus the lifetime of the implant is increased. However, the main weakness of HA lies on its poor mechanical strength that makes it unsuitable for load-bearing applications. An attractive way to produce the tougher HA is to use composite powders such as Yttria-Doped Zirconia-Hydroxyapatite (YSZ-HA) consisting of 8 mol% yttria-stabilized tetragonal zirconia (YSZ) so that the apatite phase increases the biocompatibility and zirconia (ZrO2) phase improves the strength. Y2O3 addition into zirconia can stabilize the tetragonal phase at room temperature (YSZ) and the tetragonal phase plays a major role to increase the fracture toughness. In the present study yttria-dopped zirconia powders by using ZrO(NO3)(2)center dot xH(2)O and Y(NO3)(3)center dot 6H(2)O were produced to synthesize HA-YSZ composites. In accordance with this purpose, at the first step, Ca(NO3)(2)center dot 4H(2)O, (NH4)(2)HPO4 and YSZ powders were dissolved in simulated body fluids (SBF) to obtain sol. The gelatin solutions with different concentration were added into sot to provide the gelation. Then the surfaces of Ti implants were soaked in this solution. The coating rate of Ti samples was arranged as 14 cm/s and coated implants were sintered at 900 degrees C. Structural analysis of coated powders was obtained by using XRD. Morphological examinations and coating thickness were investigated by SEM. After the sol-gel solution was dried at 80 degrees C, dried-powder was sintered at 900 degrees C. Sintered powders were analyzed by FT-IR to determine any gelatin residue.
Keywords: Dip-coating; Biomimetic Sol-gel; Y-doped Zirconia-Hydroxyapatite Composite; cp-Ti; BIOMEDICAL APPLICATIONS; Engineering; Materials Science